Subscription Cancellation in OTT Multihoming Users: An Exploratory Study Based on Experienced Benefits and Behavioral Costs - Donga Jeong; Sang Woo Lee (International Telecommunications Society (ITS), 2024)
With the rapid growth of the OTT service market and increasing competition among platforms, the phenomenon of 'multihoming'—subscribing to multiple OTT services simultaneously—is becoming increasingly prominent. Surveys indicate that while users experience benefits such as access to diverse content through multihoming, they also experience subscription fatigue due to managing multiple services. This study aims to examine how the benefits and costs experienced through multihoming influence the decision to discontinue use, based on the 'Rational Choice Behavior Model'. Particularly, this research explores the role of 'coupling', a psychological factor, in the discontinuation of multihoming. It analyses how the benefits and costs experienced by users in OTT multihoming can lead to discontinuation through psychological coupling. By applying the Rational Choice Behavior Model to OTT research, this study seeks to understand the decision-making process behind users' discontinuation of OTT multihoming. Practically, it offers insights for OTT providers on strategies to reduce the rate of multihoming attrition.
Keywords: 330; OTT Multihoming; Subscription Fatigue; Intention to stop multihoming; Coupling